Women's Scholarship in Islam And Their Contribution To The Teaching Knowledge - Abdullah A Afifi (IDRIS Darulfunun Institute, 2022)
The scholarly world is a divine devotion. It needs time and effort to be consistent and persistent in improving the understanding of society. The more literate society, the more hope for a better environment. Today's world needs more scholarly work not just to amaze the concept but also can impact society. Women's roles in education are tremendous to take learning environment from an early age. The references about women scholars are so limited that we will assume there is the little impact made. This paper shows how women's intellectual influence has made a massive contribution since the prophet Muhammad (PBUH) period. The shift in women's roles is contextual and depends on the understanding of society and the development progress of the education ecosystem itself. We hope the tremendous past work can inspire us to build an advanced learning society to improve the education process today.